2017
DOI: 10.1016/j.aprim.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Situación funcional, autopercepción de salud y nivel de actividad física en pacientes con artrosis

Abstract: In patients with OA, pain and functional capacity are the most affected dimensions. Functional status and self-rated health status are higher in active patients, regardless of the number of joints affected and their demographic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(29 reference statements)
2
1
0
2
Order By: Relevance
“…Self-perception of health assesses a concept similar to the severity index, so in our study it is the severity index measured with the EQ-5D-5L questionnaire, which shows a significant correlation that relates a worse perception of health with less physical activity, as indicated in previous studies. These data coincide with the results of other studies, identifying the higher severity index as one of the main factors negatively related to the performance of physical activity ( 5 , 34 , 35 ). Although the accuracy of the measurement of quality of life in the older adult using the EQ-5D-5L questionnaire has been questioned, suggesting its extension to other aspects of quality of life such as social contact, perception of the treatment received by others and level of independence, this tool has been recognized as adequate for comparing health-related quality of life among the older adult ( 36 ).…”
Section: Discussionsupporting
confidence: 91%
“…Self-perception of health assesses a concept similar to the severity index, so in our study it is the severity index measured with the EQ-5D-5L questionnaire, which shows a significant correlation that relates a worse perception of health with less physical activity, as indicated in previous studies. These data coincide with the results of other studies, identifying the higher severity index as one of the main factors negatively related to the performance of physical activity ( 5 , 34 , 35 ). Although the accuracy of the measurement of quality of life in the older adult using the EQ-5D-5L questionnaire has been questioned, suggesting its extension to other aspects of quality of life such as social contact, perception of the treatment received by others and level of independence, this tool has been recognized as adequate for comparing health-related quality of life among the older adult ( 36 ).…”
Section: Discussionsupporting
confidence: 91%
“…The same trend was found in non-depressives. This is in line with the resuls of a study of patients with osteoarthritis [ 32 ], where self-perceived health was higher in active patients, or those of another study of young university students, where it was concluded that those with a higher level of PA had higher levels of self-perceived physical health [ 33 ].…”
Section: Discussionsupporting
confidence: 87%
“…Un tema muy importante es que en los pacientes con GA también se ven afectadas las relaciones sociales y el bienestar emocional; lo que nos muestra una reducción de la calidad de vida. 6,11,13,14 Evaluar la calidad de vida es un primer paso imperativo para evaluar el bienestar, la progresión de la enfermedad y la eficacia de la intervención. 9,2,11 El propósito del tratamiento se centra en la mayoría de los casos en el bienestar f ísico del paciente enfocado a reducir el dolor y mejorar la función articular.…”
Section: Introductionunclassified